Digital Storytelling with Generative AI: Impact on Creativity and Engagement in Middle School Learners - Aldina, Fauzi; Gomez, Raul; Alves, Livia (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2025)
Digital storytelling is a proven pedagogy for fostering student expression, but its potential is being redefined by generative artificial intelligence (AI). While AI offers unprecedented tools for creating visual and narrative assets, its specific impact on the creativity and engagement of middle school learners requires empirical investigation. This study aimed to evaluate the impact of integrating generative AI into digital storytelling projects on the creativity and engagement levels of middle school students compared to traditional digital methods. A quasi-experimental, pre-test/post-test design was conducted with 120 middle school students. The intervention group used generative AI tools to create story assets, while the control group used standard digital tools. Creativity was assessed using a standardized rubric, and engagement was measured with the Student Engagement Instrument (SEI). The intervention group showed statistically significant gains in creativity metrics, particularly in originality and elaboration (p < .01). This group also reported significantly higher levels of cognitive and behavioral engagement compared to the control group (p < .05). Integrating generative AI into digital storytelling projects serves as a powerful catalyst, enhancing both the creative output and the active engagement of middle school learners. The technology acts as a creative partner, enabling students to realize more ambitious narrative visions.